Theoretical free energies of electron transfer, electrochemical properties, electron transfer kinetic and quantitative structural relationships studies of alkynyldihydrofullerene in [X-UT-Y][R-C60–M+] supramolecular complexes - Taherpour, Avat Arman; Tayebi-Suraki, Masomeh; Mahdizadeh, Nosratollah (European Journal of Chemistry, 2012)
The isolated pentagon rule (IPR) states that all pentagonal carbon rings are isolated in the most stable fullerenes. Fullerenes (buckministerfullerene) are a class of spherical carbon allotrope group with unique properties. Electron transfer between fullerene C60 derivatives such as alkynyldihydrofullerene (1-alkynyl-C60 carbanion) and other molecules are thought to involve the transfer of electrons between molecules surrounding the fullerene cage. One class of electron-transfer molecules has introduced as [X-UT-Y][R-C60–M+](R=tert-Bu- & H–C≡C-; M=Li & K). The supramolecular complexes [X-UT-Y] (1-9) and [R-C60–M+] (R=tert-Bu- & H–C≡C-; M=Li & K) are shown to possess a previously unreported host-guest interaction for electron transfer processes. The unsaturated, thiocrown ethers (1-9, with cis-geometry) (described as [X-UT-Y], where X and Y indicate the numbers of carbon and sulfur atoms, respectively) are a group of crown ethers that display interesting physiochemical properties in light of their conformational restriction compared to a corresponding saturated system, as well as the sizes of their cavities. Topological indices have been successfully used to construct mathematical methods that relate the structural data to the various chemical and physical properties. To establish a good relationship between the structures of 1-9 with derivatives of alkynyldihydrofullerene (1-alkynyl-C60 carbanion) as [R-C60–M+] (R=tert-Bu- & H–C≡C-; M=Li & K) in DMSO and THF solvents 12-38, an index (mcs) is utilized. This index is the ratio of the sum of the number of carbon atoms (nc) and the number of sulfur atoms (ns) with the product of these two numbers for 1-9. In this study, were investigated the relationships between this index and the first to third free energies of electron transfer (ΔGet(n); n=1-3, which is given by the Rehm-Weller equation) between 1-9 and [R-C60–M+] (R=tert-Bu- & H–C≡C-; M=Li & K) as [X-UT-Y][R-C60–M+](R=tert-Bu- & H–C≡C-; M=Li & K) supramolecular complexes in DMSO and THF solvents. The first to third free energies of electron transfer and the kinetic rate constants of the electron transfers, ΔG#et(n) and ket (n=1-3), respectively, were also calculated for [X-UT-Y][R-C60–M+] (R=tert-Bu- & H–C≡C-; M=Li & K) in DMSO and THF, in accordance with the Marcus theory.